2014
DOI: 10.1038/eye.2014.137
|View full text |Cite
|
Sign up to set email alerts
|

High intravitreal TGF-β1 and MMP-9 levels in eyes with retinal vein occlusion

Abstract: Purpose Vascular endothelial growth factor is a leading target to reduce macular oedema and improve visual acuity in patients with retinal vein occlusion (RVO), whereas the role of vascular destabilizing and fibroproliferative transforming growth factor (TGF)-b1 and matrix metalloproteinases (MMP)-2 and -9 in pathological manifestations of RVO is anticipated but less studied. Methods Undiluted vitreous samples were collected from three central RVO and one branch RVO eyes, all with neovascularization and fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…A previous by Tuuminen et al reported higher aqueous humor levels of MMP-2 and MMP-9 in RVO patients (8), which is line with our observation. MMP1 is a key collagenase and MMP2 and MMP9 are gelatinases.…”
Section: Discussion:supporting
confidence: 94%
See 2 more Smart Citations
“…A previous by Tuuminen et al reported higher aqueous humor levels of MMP-2 and MMP-9 in RVO patients (8), which is line with our observation. MMP1 is a key collagenase and MMP2 and MMP9 are gelatinases.…”
Section: Discussion:supporting
confidence: 94%
“…However, the visual outcome varies in patients. Current management of CRV is not satisfactory (6)(7)(8)(9). The mechanism of RVO remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been shown to be mitogenic for fibroblasts but inhibit proliferation of most other cell types. 2 TGFb-1 and -2 have been detected in vitreous fluid, 28,35 with higher amounts detected in patients with ocular fibroproliferative disease such as PVR and proliferative diabetic retinopathy. TGFb-1 and -2 are pro-fibrotic, 27,36 whereas TGFb-3 reduces expression of fibrotic proteins and promotes deposition of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of VEGF and IL-6 correlated with both the severity of macular edema and the extent of retinal ischemia in patients with CRVO and BRVO [Reviewed by Karia, 2010] (147) . (75,80,83,133,143,144,172,205,224,269,302) .…”
Section: A Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%